Elevation of Urinary 2-Hydroxyglutarate in IDH-Mutant Glioma. (1st February 2016) - Fathi, Amir T.; Nahed, Brian V.; Wander, Seth A.; Iafrate, A. John; Borger, Darrell R.; Hu, Ranliang; Thabet, Ashraf; Cahill, Daniel P.; Perry, Ashley M.; Joseph, Christelle P.; Muzikansky, Alona; Chi, Andrew S.
Abstract: Background: Recurrent mutations in the isocitrate dehydrogenase 1 ( IDH1 ) and IDH2 genes, which are frequent in gliomas, result in marked accumulation of the metabolic by-product 2-hydroxyglutarate (2-HG) within tumors. In other malignancies, such as acute myeloid leukemia, presence of IDH mutation is associated with elevated 2-HG levels in serum or urine compartments. Circulating 2-HG in patients with glial malignancies has not been thoroughly investigated. Methods: In this study, we analyzed 2-HG levels in the serum and urine of a large set of patients with IDH -mutant and IDH -wild-type glioma, and the cerebrospinal fluid (CSF) from a subset of this cohort. Results: We found that 2-HG was elevated in the urine of patients with IDH -mutant versus IDH -wild-type glioma, although no significant differences in 2-HG levels were observed in the serum or the small set of CSF samples obtained. Among patients with IDH -mutant glioma, 2-HG levels did not differ based on the histopathologic grade, genetic subtype ( TP53 mutant or 1p/19q codeleted), presence of a canonical ( IDH1 R132H) or noncanonical (any other IDH variant) mutation, or treatment type. Conclusion: Our finding suggests that urinary 2-HG is increased among patients with IDH-mutant gliomas, and may represent a future surrogate, noninvasive biomarker to aid in diagnosis, prognosis, and management. Abstract : Isocitrate dehydrogenase ( IDH ) gene mutations, frequent in gliomas, cause increased levels of 2-hydroxyglutarate (2-HG). 2-HG levels were found to be elevated in the urine of patients with IDH -mutant versus IDH -wild-type glioma; no significant differences in 2-HG levels were observed in the serum or the small set of cerebrospinal fluid samples obtained. 2-HG may represent a future surrogate, noninvasive biomarker to aid in diagnosis, prognosis, and management of IDH -mutant glioma.